Modelo ProLab UNITY, una propuesta sostenible para mejorar la calidad de vida de la comunidad LGBTIQ + en el Perú - Flores Guillen, Luz Estefany (2024)
This report presents UNITY, an innovative digital platform aimed at offering emotional and psychological support to the LGBTIQ+ community in Peru, a group that faces serious challenges due to high levels of discrimination and a shortage of specialized resources. UNITY arises to fill a critical gap in the offer of inclusive services, creating a safe and reliable environment that promotes the well-being of its users. In Perú, where the lack of psychological support services for this community is palpable, UNITY distinguishes itself by providing professional counseling, support groups, educational resources and safe spaces for social interaction. The project is supported by a solid marketing plan, which combines digital strategies and collaborations with local and international organizations. The in-depth interviews carried out have allowed us to capture the main market insights, guiding the development of a proposal aligned with the specific needs of the target population. The prototype and operational plan ensure that UNITY is both desirable and feasible. UNITY is projected to break even, capturing 0.5% of the target market, with an estimated annual growth of 8%. These projections reveal a Net Present Value (NPV) of S/. 3,394,295.29 and an TIR of 82.46% in five years, confirming the economic viability of the project. The platform has designed a profitable and scalable business model, which ensures its long-term sustainability. UNITY contributes to several Sustainable Development Goals (SDGs), by promoting mental health, reducing inequalities and fostering inclusive communities. With an estimated social NPV of S/.2, 968, 534.60 in the fifth year, the platform has a significant positive impact on the quality of life of LGBTIQ+ people, seeking to reduce the stigma associated with sexual orientation and gender identity and promote a more equitable and respectful.